Penguatan Posyandu Terintegerasi Dan Pembangunan Spal Di Kampung Pujo Kerto Kecamatan Trimurjo Kabupaten Lampung Tengah - Imam Santosa; Daria Br. Ginting; Arie Nugroho; Titi Astuti (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The community service program in Kampung Pujo Kerto faces significant challenges related to the sustainability of the Integrated Posyandu and the problem of stagnant household liquid waste, which has the potential to thwart ongoing initiatives. Departing from the success of the formation of the Posyandu Prima organization and training of cadres at the PPDM Poltekkes Tanjung Karang in 2023, this community service program focuses on the sustainability of integrated Posyandu and innovative solutions for handling liquid waste in order to create a healthy and sustainable environment. The main objective of the PPDM Poltekkes Tanjungkarang activity is to strengthen the integrated Posyandu and build a pilot Wastewater Drainage Channel (SPAL). The methodology used includes the preparation, implementation, and monitoring evaluation stages. The results that have been achieved include improving the skills of integrated Posyandu cadres and the construction of 10 wastewater drainage channels (SPAL), showing concrete steps towards improving environmental health and sanitation in village Pujo Kerto.